Effectiveness of pneumatically powered penetrating and non-penetrating captive bolts in stunning cattle - Octavio Oliveira, Steffan Edward [UNESP]; Gregory, Neville George; Dalla Costa, Filipe Antonio [UNESP]; Gibson, Troy John; Dalla Costa, Osmar Antonio; Rodrigues Paranhos da Costa, Mateus Jose [UNESP] (Elsevier B.V., 2018)
This study assessed the effectiveness of penetrating (PCB; 190 psi; N = 363) and non-penetrating captive bolt guns (NPCB; 210-220 psi; N = 92) to stun a total of 455 cattle (Zebu and Zebu Cross). Physical bolt parameters (momentum, kinetic energy and energy density) were evaluated. Clinical indicators of brain function were recorded after stunning (GR), after being hoisted (HO) and at the bleeding rail (BL). Physical bolt parameters (bolt velocity, momentum, kinetic energy, energy density and sectional density) were significantly higher (P < 0.001) for PCB. The need for two or more shots was more frequent for NPCB (210-220/4 29% vs. 12%, P < 0.001). Cattle were more likely to collapse at first shot with PCB (190 psi; 99%) compared to NPCB (91%; P < 0.002) which can be attributed to the higher values of bolt physical parameters. Incidence of eyeball rotation (5% vs. 1%) and righting behaviour (7% vs. 1%) were higher (P < 0.001) for NPCB (210-220 psi) at GR than PCB. The NPCB with 210-220 psi had a higher frequency of response to nostril stimulation (2% vs. 0%; P < 0.001) than PCB. Rhythmic respiration was more frequently found for NPCB with 210-220 psi at GR, HO and BL. Therefore, PCB with 190 psi was more effective in ensuring unconsciousness In cattle.
Keywords: Bolt velocity; Cattle slaughter; Rhythmic respiration; Signs of consciousness